Tissue-specific biological aging predicts progression in prostate cancer and acute myeloid leukemia - Ramakrishnan, Anitha; Datta, Indrani; Panja, Sukanya; Patel, Harmony; Liu, Yingci; Craige, Michael W.; Chu, Cassandra; Jean-Marie, Giselle; Oladoja, Abdur-Rahman; Kim, Isaac; Mitrofanova, Antonina (Frontiers in Oncology, 2023)
Chronological aging is a well-recognized diagnostic and prognostic factor in multiple cancer types, yet the role of biological aging in manifesting cancer progression has not been fully explored yet. Given the central role of chronological aging in prostate cancer incidence, here we investigate a tissue-specific role of biological aging in prostate cancer progression. Our prostate cancer-specific investigations nominated four biological aging genes (CD44, GADD45B, STAT3, GFAP) significantly associated with time to disease progression in prostate cancer in Taylor et al. patient cohort. Stratified survival analysis on Taylor dataset and validation on an independent TCGA and DKFZ PRAD patient cohorts demonstrated ability of these genes to predict prostate cancer progression, especially for patients with higher Gleason score and for patients younger than 60 years of age. We have further tested the generalizability of our approach and applied it to acute myeloid leukemia (AML). Our analysis nominated three AML-specific biological aging genes (CDC42EP2, CDC42, ALOX15B) significantly associated with time to AML overall survival, especially for patients with favorable cytogenetic risk score and for patients older than 56 years of age. Furthermore, comparison of the identified PC and AML markers to genes selected at random and to known markers of progression demonstrated robustness of our results and nominated the identified biological aging genes as valuable markers of PC and AML progression, opening new avenues for personalized therapeutic management and potential novel treatment investigations.